'An inalienable prerogative of a liberated spirit': postulating American mathematics. Issue 3 (1st September 2020) - Abrams, Ellen
Abstract : In the early twentieth century, researchers in the United States engaged with foundational studies in mathematics by building and evaluating postulate systems. At the same time, their contemporaries were evaluating the meaning and politics of knowledge more broadly. This article argues that the study of postulates in the United States was tied to important Progressive Era questions about the nature of knowledge, the status of the knower, and the development of American Pragmatism. While most investigations of postulate studies have considered their implications within mathematical research and education, this article looks instead to the role of postulate studies in the professionalization of mathematics in the United States and to its cultural status more broadly.